A proteomic approach of the different environmental conditions of Listeria monocytogenes. (20th October 2021) - D'Onofrio, F; Krasteva, I; Schirone, M; Torresi, M; Tittarelli, M; Pomilio, F; Iannetti, L; Di Febo, T; Luciani, M
Abstract:  : Listeria monocytogenes is the ubiquitous food-borne pathogen which causes listeriosis, a disease with a high mortality rate, mostly transmitted through contaminated ready-to-eat foods. To better understand the systemic response of L. monocytogenes exposed at 3 environmental factors (T, pH and NaCl), the proteome of L. monocytogenes strain NRG 1749-2016, isolated from a meat product, was investigated to identify differences in the protein patterns of such pathogen. Four different conditions were carried out as follows: A) T 37 °C, pH 7.0, NaCl 0.5%; B) T 37 °C, pH 5.5, NaCl 7%; C) T 12° pH 7, NaCl 0.5%; D) T 12 °C, pH 5.5, NaCl 7%. The proteins belonging to cytosol (C1) and vesicles (C2) were isolated and purified by CelLytic B Cell Lysis Reagent and CelLytic IB Inclusion Body Solubilization Reagent according manufacturer's instructions. The analysis were conducted by SDS PAGE and Immunoblotting techniques. The protein concentrations were evaluated by Pierce BCA Protein Assay Kit. From preliminary results, the protein banding patterns generated by 1D SDS PAGE were found to be different at visual observation for C1 and C2, in A, B, C and D conditions. The presence of specific antigen-antibody immunocomplexes (Ag-Ab ICs) was identified by Immunoblotting, in C1 at 100, 60, 55, 35 and 25 kDa for all incubated conditions with a positive serum to L. monocytogenes. As regards C2, Ag-Ab ICs at 110 kDa were observed in A and B, Ag-Ab ICs at 80 kDa in C and D, Ag-Ab ICs at 60 kDa in A and D, while Ag-Ab ICs at 40 and 30 kDa in all conditions. The analysis of the proteome profiles shows an intra-strain variation in the protein patterns produced by L. monocytogenes during the adaptation at different environmental conditions. Further analysis will be carried out to better understand the systemic response of L. monocytogenes, in particular in order to characterize the immunogenic proteins highlighted by Immunoblotting and their role in the virulence expression of such pathogen. Key messages: Understand how L. monocytogenes adapts physiologically to different environmental factors. Development of new detection method of L. monocytogenes and prevention strategies for listeriosis outbreaks.